Advanced Gastric Cancer in a Young Male Patient - Febyan Febyan; Ruswhandi Martamala; Diany Nurliana; Salmi Salmi (The Indonesian Society for Digestive Endoscopy, 2018)
Gastric cancer remains the second most common GI cancer in the world, and is usually found in men, especially those over 50 years of age. Gastric cancer is a multifactorial disease resulting from the interactionbetween genetic and environmental factors at the stomach mucosa level. The diagnosis is made by endoscopic biopsy. The high frequency of late diagnosis or advanced stages accounts for the overall poor prognosis for this tumor. Surgery is the most frequently employed modality for both cure and palliation. However, most patients present with advanced disease that is incurable. We reported a rare case of young male patient aged 24 years old with advanced gastric adenocarcinoma. The main clinical features were epigastric pain, vomiting, melena and weight loss. An abdominal mass was palpable on physical examination. Endoscopy showed a giant tumor mass causing gastric outlet obstruction, that appear edematous, there were hemorrhagic lesions. The histopathologic examination revealed poorly differentiated adenocarcinoma. Palliative resection could not be performed because the tumor tightly adhered to adjacent structures. Jejunostomy or nasojejunostomy tube were performed to allow enteral nutrition. Best supportive care is very important to improve the quality of life.